Robust adaptive finite-time tracking control for Intervention-AUV with input saturation and output constraints using high-order control barrier function. (15th January 2023) - Hou, YongKang; Wang, Hai; Wei, Yanhui; Iu, Herbert Ho-Ching; Fernando, Tyrone
Abstract: The Intervention-Autonomous Vehicle (I-AUV) as the effective operation equipment in the deep sea is suppressed to the external and physical constraints, which makes it challenging to achieve underwater missions. Aiming at the trajectory tracking control of I-AUV with input saturation and output constraints, a higher-order control barrier function-quadratic program (HoCBF-QP) based control scheme is proposed in this paper considering the uncertainties, disturbance and dynamic interaction. Firstly, a robust adaptive control is presented to track the desired trajectory in a finite time, where a feedback control term, based on the continuous terminal sliding mode (TSM) technique, is designed to improve the tracking performance under the uncertainties, disturbance and dynamic interaction. Secondly, a time-varying HoCBF is further developed to handle the high relative degree time-varying output constraints, then the multiple high-order control barrier functions can bring a family of safety-critical control input to preserve the reachability of AUV posture and joints motion. Thirdly, a convex quadratic program (QP)-based separation control frame is designed to conduct the tracking problem and output satisfaction separately. Due to its globally optimal advantage, the proposed control design provides a flexible frame to track objectives for the constrained I-AUV systems. Comparable simulation results demonstrate the fast convergence, robustness and high tracking accuracy of the proposed HoCBF-QP control for I-AUV systems with constraints. Highlights: Continuous terminal sliding mode-based robust adaptive control ensures finite-time convergence. The higher-order control barrier function (HOCBF) guarantees that the high relative degree constraints are never violated. A HOCBF-quadratic program (QP) control frame is designed to track trajectory forI-AUV under constraints and disturbances. Closed-loop stability proof of HOCBF-QP control is rigorously given via Lyapunov theory. Comparative simulations show the excellent control performance of the HOCBF-QP control.